Flouting Maxim Analysis in ‘The Wonderful Story of Henry Sugar’ Movie - Alhafidz, Nabil; Silaen, George; Zannah, Khoirunnisa ul; Natsir, Muhammad (EDUCTUM: Journal Research, 2024)
The aim of this research is to identify maxim flouting in the film "The Wonderful Story of Henry Sugar". During data collection, researchers analyzed the film’s dialogues. Literature reviews from various journals and related books were used to supplement the existing literature and validate the collected data. The successfully collected data was analyzed using Paul Grice’s cooperative principle theory. The analysis revealed a total of 7 maxim floutings, which included the four maxims identified by Grice: maxim of quality, maxim of quantity, maxim of relevance, and maxim of manner. These violations occurred simultaneously and separately. This finding also demonstrates that the frequency of maxim flouting is not evenly distributed throughout the film’s dialogue.